Misconduct or negligence of employees leading to financial losses: How can employers mitigate damage or recover losses - Ali Mohamed, Ashgar Ali (2016)
It is a fact that an employee can be dismissed from employment after due inquiry when he was found negligent in respect of his duties or he has committed an act or acts of serious misconduct. However, what are the rights of the employer when such negligence or misconduct has caused damage and/or financial losses to the employer? Even if the employer can recover damages or losses, are such claims recoverable from the employee through salary deduc- tion? Come listen to our distinguished speaker, who will provide guidance in this subject matt